When Persistence Signals Exit: Identity, Legitimacy, and Indigenous Educational Persistence - Simons, Aggey (Université d'Ottawa | University of Ottawa, 2026)
Why does scholarship aid sometimes fail to increase postsecondary persistence among Indigenous students, and in some settings even reduce it? Because schooling has historically been associated with residential schools, boarding schools, and assimilationist state projects, persistence can signal not only investment in human capital but also exit from the home community. I model persistence as a signaling game between a student and the home community in which community support feeds back into the student's payoff from schooling. The student privately knows whether the orientation type is community-oriented or exit-oriented, while the community observes persistence and decides whether to extend support. The baseline model yields four implications. First, when schooling is culturally alienating, students most attached to the community may be the most likely to leave. Second, scholarships can crowd out persistence by weakening the inference that persistence reflects community-oriented motives. Third, Indigenous institutional design raises persistence directly and by preserving legitimacy. Fourth, legitimacy thresholds generate multiple equilibria. Extensions show that scholarship crowd-out is not generic and that sponsor mission shapes the mix between cash aid and institutional legibility. I also document descriptive patterns consistent with the mechanism: large attainment gaps alongside substantial scholarship infrastructure, stronger persistence in tribally governed and culturally grounded institutions, and a strong association between support environments and educational completion. The policy implication is not that financial aid is unimportant, but that it is most effective when combined with institutional design and support structures that make persistence legible as community-serving.
Keywords: Indigenous Education; Educational Persistence; Identity and Signaling; Scholarships; Institutional Design